An end-to-end automated platform process for high-throughput engineering of next-generation multi-specific antibody therapeutics. Issue 1 (1st January 2021) - Furtmann, Norbert; Schneider, Marion; Spindler, Nadja; Steinmann, Bjoern; Li, Ziyu; Focken, Ingo; Meyer, Joachim; Dimova, Dilyana; Kroll, Katja; Leuschner, Wulf Dirk; Debeaumont, Audrey; Mathieu, Magali; et al.
ABSTRACT: Next-generation multi-specific antibody therapeutics (MSATs) are engineered to combine several functional activities into one molecule to provide higher efficacy compared to conventional, mono-specific antibody therapeutics. However, highly engineered MSATs frequently display poor yields and less favorable drug-like properties (DLPs), which can adversely affect their development. Systematic screening of a large panel of MSAT variants in very high throughput (HT) is thus critical to identify potent molecule candidates with good yield and DLPs early in the discovery process. Here we report on the establishment of a novel, format-agnostic platform process for the fast generation and multiparametric screening of tens of thousands of MSAT variants. To this end, we have introduced full automation across the entire value chain for MSAT engineering. Specifically, we have automated the in-silico design of very large MSAT panels such that it reflects precisely the wet-lab processes for MSAT DNA library generation. This includes mass saturation mutagenesis or bulk modular cloning technologies while, concomitantly, enabling library deconvolution approaches using HT Sanger DNA sequencing. These DNA workflows are tightly linked to fully automated downstream processes for compartmentalized mammalian cell transfection expression, and screening of multiple parameters. All sub-processes are seamlessly integrated with tailored workflow supporting bioinformatics. As described here, we used this platform to perform multifactor optimization of a next-generation bispecific, cross-over dual variable domain-Ig (CODV-Ig). Screening of more than 25, 000 individual protein variants in mono- and bispecific format led to the identification of CODV-Ig variants with over 1, 000-fold increased potency and significantly optimized production titers, demonstrating the power and versatility of the platform.